A green and scalable route to yield porous carbon sheets from biomass for supercapacitors with high capacity. Issue 3 (3rd January 2018) - Wang, Cunjing; Wu, Dapeng; Wang, Hongju; Gao, Zhiyong; Xu, Fang; Jiang, Kai
Abstract : A green route is developed to prepare hierarchical porous carbon sheets (HPCS) from biomass directly under air atmosphere without inert gas protection. The as-prepared HPCS with ultra-thin structure, rich O doping sites and large SSA demonstrate excellent specific capacitance and stability when used in supercapacitor. Abstract : A green and scalable route is developed to prepare hierarchical porous carbon sheets (HPCS) from biomass (cornstalk) directly under an air atmosphere instead of inert gas protection. In addition, the method adopts non-toxic NaCl and KCl mixed salt as reaction media to regulate the activation process, which avoids the corrosive and poisonous KOH and ZnCl2 reagents. Meanwhile, the porous structures of HPCS can be well-manipulated by the salt templates and the etching effects of the oxygen atom as well as the high energy molten salt media. The as-obtained HPCS consist of an ultra-thin sheet structure (∼4.6 nm in thickness) and abundant hierarchical pores, which facilitates electrolyte diffusion and ion transfer. In addition, the high specific surface area of 1588 m 2 g −1 provides sufficient active sites and the rich O doping introduces pseudocapacitance. Therefore, the as-prepared HPCS exhibit a high specific capacitance of 407 F g −1 at 1 A g −1 in a three-electrode system. Moreover, the assembled symmetric supercapacitor in a two-electrode system also exhibits an outstanding specific capacitance of 413 F g −1 at 0.5 A g −1, an excellent rate capacity and a long-term cycling stability with 92.6% of initial capacitance retention after 20 000 cycles at 5 A g −1, which are comparable to those of the porous carbons activated with traditional methods. It is expected that this green and facile technique could serve as an effective and scalable method to prepare optimized HPCS with tunable porous structures from biomass for electrochemical energy storage applications.